Związki ekonomii i etyki w poglądach Mohandasa Gandhiego - Matera, Rafał (Annales. Etyka w Życiu Gospodarczym, 2013)
The aim of the article is to present the economic thought of Mohandas Karamchand Gandhi with respect to ethical aspects. There are lots of statements and remarks about the relations of ethics and economics in Gandhi’s writings. In his opinion, both areas should be treated as integrated. That is why it is worth analysing Gandhi’s views on various economic matters. Only a selected presentation was possible because it was difficult to find cohesion in his socio-economic system. One of the hypothesis underlined is that it is even risky to write about Gandhi’s united system. Generally his economic thought was not a part of economics as a discipline. Nevertheless it is not a reason to relinquish studies of it. Because of the fact that many remarks linked with microand macroeconomics are of considerable value, they can be used to research economic changes in India in 20th century or to study the attitude of Indian society towards those changes. The main source of the paper was the autobiography ‘The Story of My Experiments with Truth’ published in 1925. More of Gandhi’s economic thought can also be found in the work ‘Hind Swaraj’ from 1909 and in the lecture ‘Does Economic Progress Clash with Real Progress?’ from 1916.